White Matter Abnormalities in Patients With Parkinson's Disease: A Meta-Analysis of Diffusion Tensor Imaging Using Tract-Based Spatial Statistics - Wei, Xia; Luo, Chunyan; Li, Qian; Hu, Na; Xiao, Yuan; Liu, Nian; Lui, Su; Gong, Qiyong (Frontiers in Aging Neuroscience, 2021)
Background: Tract-based spatial statistics(TBSS) studies based on diffusion tensor imaging (DTI) revealed the extensive abnormalities in white matter(WM) fibers of Parkinson disease (PD); however, the results were inconsistent. Therefore, a meta-analytical approach was used in this study to find the most prominent and replicable WM abnormalities of PD. Methods: Online databases were systematically searched for all TBSS studies comparing fractional anisotropy (FA) between PD and controls. Subsequently, we performed the meta-analysis by using a coordinate-based meta-analytic software called seed-based d mapping (SDM). Meanwhile, meta-regression was performed to explore the potential impact of the FA alteration on the clinical characteristics of PD. Results: 21 datasets including 746 patients with PD and 555 healthy controls were incorporated into the current study. FA reduction was identified in the body of Corpus callosum(CC) and the left inferior fronto-occipital fasciculus(L.IFOF). Both of them maintained significance in the sensitivity analysis. No FA increase was identified. No statistically significant association between the patient’s clinical characteristics and FA alteration was found. Conclusions: Though some limitations existing, DTI is regarded as a valid way to learn the pathophysiology of PD. It could be more beneficial to integrate DTI parameters with other MRI techniques to explore the brain degeneration in PD.